My Wondering “Are EFL Excited Learning toward Interactive Media?” The Perception Study from EFL - Bandono, Adi; Kurniati, Fadhika; Wati, Sundari; Rahmawati, Yuliana; Maulifah, Umul; Purwaningsih, Elis Dwi; Winarni, Winarni (Universitas Trunojoyo Madura, 2025)
Interactive Learning Multimedia is a technological tool that can be effectively utilized as a learning resource. This type of media not only supports the instructional process but also contributes positively to students' learning outcomes. The use of digital platforms enables teachers to express their creativity and tailor their teaching approaches to align with students' learning styles and interests. Implementing Google Sites as a platform for delivering interactive multimedia facilitates more effective learning and enhances students’ understanding of the material. This study aims to describe students’ perceptions of learning procedural texts through Interactive Learning Multimedia based on Google Sites. A qualitative approach with a phenomenological design was employed. Data were gathered through observations of students’ active participation and motivation, along with reflection sheets covering their perceptions, understanding, and evaluations of the media. Data analysis was conducted from the outset of data collection, involving reduction, presentation, and conclusion drawing. The findings revealed that students held highly positive perceptions toward the use of interactive media. They reported feeling happy, interested, and motivated while learning procedural texts through this medium.